Neurofeedback training content for treatment of stress - Hafeez, Y. (Institute of Electrical and Electronics Engineers Inc., 2017)
Stress is one of the major problems in society and is being treated using medicine and neurofeedback therapy. Neurofeedback therapy is usually successful. The contents as stimuli for neurofeedback training are not available for stress and anxiety. This paper focuses on giving a comprehensive and critical summary of available contents for neurofeedback training. It also establishes a need for the development of content as a stimulus for neurofeedback which trains the subject on how to control his brain activity, especially in stress condition. The developed content consists of audio and game. The game is used to reduce the power of high-beta brain activity and the audio is used to enhance the amplitude of alpha brainwaves in left-prefrontal lobe. The experimental results show significant improvement in reducing stress level. The outcome is a proposed content for neurofeedback training to reduce stress, and it also improves the neurofeedback training efficacy. © 2016 IEEE.